Reevaluating Reality through the Experience of Games: The Gamification of Web Novels through the Example of Yan Liangyu's Ghost Server Legion. - Wang, Yusu; Keller, Jeffrey; Jiang with, Bai; Yang, Renren (Chinese Literature & Thought Today, 2024)
The gamification of Chinese web novels not only signifies that video games have become a popular theme in Chinese Internet literature or that Chinese Internet literature has borrowed elements from video games, but it also indicates a transformation in the entire narrative paradigm that concerns both character development and plot structure. Taking Yan Liangyu's web novel Ghost Server Legion, which features online gaming as its theme, as an example, the main characters in the novel are "semi-autonomous characters" defined by their moe attributes. The world-building in the novel no longer aims to mimic reality but instead constructs a self-contained and smoothly operating "parallel world" akin to a computer system. The character setup and the fictional world setting comprise the two main pillars that generate stories in gamified web novels. Understanding our social realities through the lens of a "parallel world" also reflects the lived experiences and emotional structures of a new generation of online authors and readers, revealing their new vision for the world emergent behind what appears to be a cynical attitude toward life.